2009
DOI: 10.1097/ajp.0b013e3181878f87
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive and Non-nociceptive Hypersensitivity at Latent Myofascial Trigger Points

Abstract: These results confirm the existence of nociceptive hypersensitivity at latent MTrPs and provide the first evidence that there exists non-nociceptive hypersensitivity (allodynia) at latent MTrPs. Finally, the occurrence of referred muscle pain is associated with higher pain sensitivity at latent MTrPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 28 publications
2
54
0
1
Order By: Relevance
“…19,28 The existence of nociception in latent TrPs has been recently confirmed in a study demonstrating the existence of nociceptive (hyperalgesia) and nonnociceptive (allodynia) hypersensitivity at latent TrPs. 33 Other researchers have reported that nociceptive stimulation of latent TrPs induced an attenuated skin blood flow response, 52 not increased by maneuvers that activate sympathetic outflow, 30 suggesting sympathetic vasoconstrictor activity elicited by nociceptive stimulation of latent TrPs. Finally, there is also evidence that latent TrPs induced motor disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…19,28 The existence of nociception in latent TrPs has been recently confirmed in a study demonstrating the existence of nociceptive (hyperalgesia) and nonnociceptive (allodynia) hypersensitivity at latent TrPs. 33 Other researchers have reported that nociceptive stimulation of latent TrPs induced an attenuated skin blood flow response, 52 not increased by maneuvers that activate sympathetic outflow, 30 suggesting sympathetic vasoconstrictor activity elicited by nociceptive stimulation of latent TrPs. Finally, there is also evidence that latent TrPs induced motor disturbances.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Researchers around the world have investigated various aspects of MTrPs, including their specific etiology, pathophysiology, histology, referred pain patterns, and clinical applications. [3][4][5][6][7][8][9] The existing literature 1,2 has suggested that the presence of MTrPs in a muscle may lead to weakness. Inhibition of muscle activity has been seen in the upper trapezius after experimentally induced pain.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] Such altered physiology may affect a muscle's capacity to generate force and, therefore, its strength. Latent MTrPs are clinically significant because they remain clinically quiescent, such that a person will not even be aware of the presence of a trigger point that may render him or her weaker and more susceptible to fatigue.…”
Section: (P1)mentioning
confidence: 99%
See 1 more Smart Citation
“…61 It is important to note that allodynia, or pain in response to a nonnociceptive stimulus, has been established only in regard to tactile or cutaneous stimulus of the skin (eg, brushing sensation) 45 (FIGURE), due to the difficulty of assessing this modality in deep tissues. 34 Therefore, the presence clinically of mechanical (tactile) allodynia in relation to musculoskeletal injury is associated with central sensitization.…”
Section: Pain-associated Hypoesthesia and Allodyniamentioning
confidence: 99%